(untitled) (Jurnal Ipteks Terapan, 2023)
The purpose of the study was to test and analyze taxes, Leverage, company size and Exchange Rate on transfer Princing decisions in mining sector companies listed on the Indonesia Stock Exchange for the period 2019-2021 using quantitative research methods. Population is a mining sector company listed on the Indonesia Stock Exchange for the period 2019-2021. The population in this study amounted to 85 mining companies and a sample of 19 companies. Sampling is determined by purposive sampling method. Data analysis techniques using multiple linear regression analysis. The results showed that the tax has no effect on the Transfer Princing decision, Leverage has no effect on the Transfer Princing decision, the size of the company has a positive and significant effect on the Transfer Princing decision, the Exchange Rate has no effect on the Transfer Princing decision and tax, Leverage, company size and Exchange Rate has no effect on the Transfer Princing decision.